Comparing the Effectiveness of 7-Day vs 9-Day CIDR Placement for the Treatment of Postpartum Anestrus in Crossbred Dairy Cows - Shrestha, Niraj; Gautam, Gokarna; Devkota, Bhuminand (Journal of Agriculture and Forestry University, 2025)
This study was conducted to compare the effectiveness of duration of Controlled Internal Drug Release (CIDR) placement in CIDR-PGF2α-GnRH protocol for the treatment of postpartum anestrus in dairy cows. Forty cows that were not detected in estrus at least until 60 days postpartum were selected and divided randomly into two treatment groups. The CIDR device containing 1.9 g progesterone was placed into the vagina of cows for seven days (T1, 7-day group, n=20) and 9 days (T2, 9-day group, n=20). One day before CIDR removal, all the cows were injected with PGF2α analogue (Cloprostenol 500 μg). In both groups, GnRH analogue Buserelin 20 mcg was injected intramuscularly 48 hours after CIDR removal. Then cows were artificially inseminated at fixed time (FTAI) 16-20 hours after GnRH injection. Both the estrus expression and the pregnancy rates were similar between 9-day and 7-day groups. Overall estrus expression and pregnancy rates were 97.5%, and 45%, respectively. None of the factors influenced the estrus expression and pregnancy outcomes except that the ovarian cyclicity at the start of protocol tended to affect the pregnancy rate (P=0.06). In conclusion, while applying CIDR-PGF2α-GnRH protocol, the application of CIDR for 7 days and 9 days were equally effective on inducing estrus and pregnancy outcome in postpartum anestrous cows, but the pregnancy outcome depended on the status of ovarian cyclicity at the start of the protocol.